Exploring the complexity of being both a psychologist and mother: a psychosocial study - Sheridan, Gillian Lorraine (My University, 2017)
Psychodynamic psychotherapists through their vocational training, and especially through developmental and psychoanalytic theories, are exposed to intense discursive and theoretical psychological models of ideal motherhood and childhood development that they use to inform their therapeutic practice. How this knowledge impacts their mothering experience and practice has not been explored. This study examines how the identities of psychotherapist and mother inform, shape, enrich and conflict with one another, for a group of nine psychodynamic psychotherapist mothers who are based in Johannesburg, South Africa. Primarily, the findings of this study suggest that the identity shifts involved in becoming both a psychotherapist and a mother are a continuous process. Alongside the negotiation of the relational demands of an infant, psychotherapist mothers, in particular, experience transitions in their relationships to theory. The voice of theory, which was found to act as a third that is analytic and/or anti-analytic, was a very important theme that was found to influence their mothering experiences and identities. The experience appears to be one of constantly evolving re-integration. Overall, the challenge for psychotherapist mothers is to reflect on their relationships to theory as a psychotherapist, in order to acknowledge and explore those aspects that feel punitive and those that feel helpful.
A research project submitted in partial fulfilment of the requirements for the degree of MA Clinical Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2017
Keywords: Psychodynamic psychotherapy--Study and teaching--South Africa; Psychotherapists--South Africa; Women--Mental health--South Africa; Women--South Africa--Psychology